A ação inibitória enquanto tutela diferenciada autônoma - Bovino, Marcio Lamonica (2016)
This thesis main objective, already under the Law 13.105/2015, is to propose pure preventive inhibitory or mandatory protection on threat of the illegal act and of abuse of rights. We seek to frame the intention of committing an abuse of rights as the foundation of inhibitory or mandatory individual judicial protection. The challenges are based on the framework of the illegal act despite the actual existence of damage, through the evidence of the intention of the exercise clearly beyond the limits imposed by economic or social order for the good faith or the good morals that the rule imposes, ending the race the probability of the right and the danger of harm or risk to the fruitful result of the process, as the basis of the request for early or injunctive interim injunction. The new Code of Civil Procedure (NCPC) which will come into force on March 16, 2016 (Law 13105 of March 16, 2015), deals with court injunctions guardianships the sole paragraph of Article 497, stating that the action that has the engaged in providing do or not do, the judge if the relief sought, grant specific protection to deter, prevent the repetition or even seeking the removal of illegal (not to be confused with prevention) regardless of the demonstration of the occurrence of damage or of fault or willful misconduct. As it turns out , the legislator has standardized , albeit not fully fit in our view, the three (3) categories of inhibitory: a) preventive inhibitory (also known as pure inhibitory protection); b) inhibitory protection to stop the repetition e c) inhibitory protection to stop the continuation of the illegal act. We feels the convenience of adoption of preventive inhibitory or mandatory protection as an autonomous differentiated judicial protection, not just one of the possible inhibitory effect of the sentence currently treated in Chapter XIII of Title I of Book I of the New Civil Procedure Code (NCPC). We suggest the adoption of inhibitory technique as an autonomous differentiated judicial protection, proposing legislative changes to the NCPC which will come into force on March 16, 2016